Post-Civil Code Contract Law Update: The Urgency of a New Codification in a Digital Society - Rohana, Layli; Virdaus, Saivol; Pratama , Topan Yulia (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Contract law codified in the nineteenth century was constructed on analog assumptions that presupposed physical objects, direct party interaction, and manual execution of agreements. Specific Background In Indonesia, the Civil Code as a colonial legacy increasingly fails to accommodate electronic transactions, digital objects of obligations, smart contracts, digital evidence, and multiparty relationships mediated by online platforms within a rapidly expanding digital economy. Knowledge Gap Existing provisions of the Civil Code do not systematically recognize electronic consent, automated contractual mechanisms, platform-based legal relations, or the probative value of digital evidence, resulting in normative gaps and legal uncertainty. Aims This study aims to examine the structural and substantive limitations of the Civil Code in the digital era and to formulate the urgency and direction of a new codification of contract law that aligns with contemporary technological realities. Results The analysis demonstrates that the Civil Code remains analog-oriented, lacks recognition of smart contracts and digital legal objects, provides no integrated framework for electronic evidence, and is unable to explain multiparty contractual relations governed by digital platforms and algorithms. Novelty This study articulates a comprehensive post-Civil Code codification model that integrates structural reform, recognition of smart contracts, digital consumer protection, and Online Dispute Resolution within a single coherent framework. Implications The proposed codification offers a systematic legal foundation to support Indonesia’s digital transformation, harmonize national contract law with international standards, and strengthen legal certainty in digital transactions. Highlights: The existing Civil Code framework remains bound to analog legal assumptions incompatible with digital transactions. Smart contracts, digital evidence, and platform-based relations lack systematic legal recognition. A unified post-Civil Code codification is required to align national contract law with digital economic development. Keywords: Contract Law Reform, Digital Contracts, Smart Contracts, Legal Codification, Online Dispute Resolution